Facilitating solutions to conservation management challenges through an understanding of human perceptions of nature and wildlife - Dietsch, Alia, author; Teel, Tara L., advisor; Manfredo, Michael J., advisor; Henry, Kimberly L., committee member (Colorado State University. Libraries, 2010)
Natural resource managers traditionally relying on biological expertise to understand and respond to today's conservation challenges (e.g., biodiversity loss, habitat fragmentation, climate change) are finding increased impetus for utilizing social sciences to inform decision-making. All too often, management decisions have been unsuccessful when they failed to address the polarizing values of stakeholders, the economic and political context of decisions, and the cultural significance of resources to local people. An understanding of these social considerations can be facilitated by an examination of human-nature and human-wildlife relationships, which often form the basis for conflict over management issues. This thesis presents two manuscripts designed to contribute to this area of inquiry by considering how public opinion may be influenced by broader conceptions of the natural environment. Such perceptions of nature are further influenced by ideology, or the way people assess meaning to their lives through consensually-held beliefs. Drawing upon Cultural Theory and the Myths of Nature, Chapter II of this thesis explores how people think about nature in three distinct areas of the western United States. To better understand such human-nature relationships, we explored a new measurement approach for capturing the Myths of Nature. Consistent with our objectives, we tested such an approach and found that five distinct perspectives regarding nature exist; that these perspectives are consistent with the Myths of Nature literature; and that results are stable across three study areas. Chapter III outlines a need for natural resource agencies wanting to ensure continued public support to have a better understanding of the diverse publics they represent. Two social science approaches (i.e., wildlife value orientation theory and the Myths of Nature) explore the influence of ideology on conflicting beliefs related to wildlife and wildlife use. Consistent with hypotheses, wildlife value orientations were found to be related to the Myths of Nature, indicating they likely draw upon similar ideologies (e.g., egalitarianism). Additionally, results indicated that people believing in a myth of Nature is Ephemeral were significantly less accepting than others of lethal control of wildlife, whereas as those believing in a myth of Nature is Benign were more accepting of lethal control. Findings as a whole corroborate that ideology, as reflected in value orientations about wildlife and the Myths of Nature, influences human thought about wildlife use, and that human thought about the natural environment can be used to enhance our understanding of public attitudes and behaviors in a wildlife-related context.
Department Head: Michael J. Manfredo.
Keywords: Wildlife management -- West (U.S.) -- Public opinion; Wildlife management -- West (U.S.) -- Statistics; Natural resources -- Management -- Public opinion; Natural resources -- Management -- Statistics